Perbedaan Penggunaan Media Digital Dan Aktivitas Jasmani Siswa Sekolah Dasar Di Daerah Perkotaan Dan Pedesaan Kabupaten Banyumas - Imbang Safidhia Ramadhan; Yudha Febrianta (Journal on Education, 2024)
This research aims to determine differences in the use of digital media and physical activity of elementary school students in urban and rural areas of Banyumas Regency. This research uses a comparative quantitative descriptive method with data collection techniques using a questionnaire. The research results show that the use of digital media in urban areas is higher than in rural areas, while the physical activity of students in rural areas is higher than in urban areas. Excessive use of digital media has a negative effect on students' physical activity. This research provides insight into the importance of managing digital media use to increase students' physical activity.